Preparation method and application of P element coated lithium-rich manganese positive electrode material

By uniformly covering the P element on the surface of the lithium -rich manganese, the problem of the traditional lithium -rich manganese positive material in the cycle is solved, the problem of fast attenuation and poor structural stability in the cycle, which significantly improves the battery discharge ratio and cycle stability performance Essence

CN119370912APending Publication Date: 2025-01-28XIAN TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411270758.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Traditional lithium-rich manganese positive electrode materials have problems such as fast capacity decay and poor structural stability during the circulation process, which limits their commercial application.

Method used

Through simple and fast craftsmanship, a separate sintering method is used to uniformly cover the P element on the surface of the lithium -rich manganese, which avoids the problem of unevenly covered and structural changes in traditional processes.

Benefits of technology

The uniform covering of the P element is achieved, which improves the battery discharge ratio capacity and circulation stability performance, and is significantly better than the battery of ordinary lithium -rich manganese.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119370912A_ABST
    Figure CN119370912A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a P element coated lithium-rich manganese positive electrode material, and the preparation method comprises the following steps: dissolving a lithium source, a nickel source, a cobalt source and a manganese source in water according to a molar ratio of Li: Ni: Co: Mn = 1.53: 0.165: 0.165: 0.665, and adding a complexing agent to obtain a precursor solution; performing high-temperature spray drying on the precursor solution to obtain precursor powder of the material; sintering the precursor powder at a high temperature of 1000 DEG C for 20 minutes to obtain a lithium-manganese-rich positive electrode powder material; and putting the two quartz crucibles respectively filled with the lithium-rich manganese powder and the P source into a tubular furnace for sintering to obtain the lithium-rich manganese-based positive electrode material coated with the P element. By a simple and rapid process, uniform coating of P element is realized, and as a positive electrode material of a lithium ion battery, the specific discharge capacity of the battery is improved, and the cycle stability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium-ion battery electrode materials, and specifically relates to a preparation method and application of a P-element coated lithium-manganese-rich positive electrode material. Background Art

[0002] At present, facing the dual challenges of fossil energy depletion and increasing environmental pollution, the world is in a critical period of energy structure transformation. In this context, building a safe, efficient, clean and low-carbon modern energy system has become an important strategy for national development, among which the utilization of renewable energy and the development of energy storage technology are particularly critical. As a bridge connecting energy production and consumption, the energy storage system plays an irreplaceable role in improving energy utilization efficiency, ensuring energy security, and promoting the consumption of renewable energy. With the continuous increase in the proportion of renewable energy, the demand for energy storage systems is becoming increasingly urgent.

[0003] Lithium-ion batteries are widely used in energy storage for new energy vehicles and portable electronic devices due to their high energy density, long cycle life, and environmental friendliness. However, with the continuous expansion of application areas and the continuous improvement of performance requirements, the positive electrode materials of traditional lithium-ion batteries have gradually exposed their shortcomings in terms of capacity and cycle stability, making it difficult to meet market demand. As the core component of lithium-ion batteries, the performance of positive electrode materials directly determines the overall performance of the battery. Lithium-manganese-rich positive electrode materials have attracted much attention due to their high specific capacity and high output voltage, but they have problems such as fast capacity decay and poor structural stability during the cycle, which limits their commercial application.

[0004] The surface coating modification of lithium-rich manganese cathode materials is expected to improve the charge-discharge specific capacity and cycle stability of the materials. However, most of the traditional coating processes mix the lithium-rich manganese cathode materials and modifiers by ball milling or solution stirring, and finally form a coating layer structure by sintering. On the one hand, this traditional process has uneven coating, which makes the coating effect not good and affects the performance. On the other hand, the coated material easily induces structural changes in the cathode material, which reduces the electrochemical performance. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a preparation method and application of a P-element-coated lithium-manganese-rich positive electrode material, which achieves uniform coating of the P element through a simple and quick process, increases the battery discharge capacity, and improves the battery cycle stability.

[0006] The technical solution of the present invention is:

[0007] A method for preparing a P-element coated lithium-rich manganese-based positive electrode material comprises the following steps:

[0008] Step 1: dissolving a lithium source, a nickel source, a cobalt source, and a manganese source in water at a molar ratio of Li:Ni:Co:Mn=1.53:0.165:0.165:0.665, and adding a complexing agent to obtain a precursor solution;

[0009] Step 2: obtaining a precursor powder of the material by high temperature spray drying the precursor solution;

[0010] Step 3: sintering the precursor powder at 1000° C. for 20 min to obtain a lithium-rich manganese positive electrode powder material;

[0011] Step 4: Put the lithium-rich manganese cathode material powder obtained in step 3 and the P source into two different quartz crucibles according to a mass ratio of 1:20-1:25;

[0012] Step 5: Put two quartz crucibles respectively filled with lithium-rich manganese powder and P source into a tube furnace for sintering, the crucible filled with P source is placed near the air inlet side, and the crucible filled with lithium-rich manganese powder is placed near the air outlet side;

[0013] Step 6: Open the gas valve of the tubular furnace and continue to introduce nitrogen; calcine at 250°C for 1 hour, and after natural cooling, obtain a lithium-rich manganese-based positive electrode material coated with P element.

[0014] Furthermore, in step 1, the molar volume ratio of lithium ions in the lithium source to water is 0.23 mol / L.

[0015] Furthermore, in step 1, the molar ratio of lithium ions in the lithium source to the complexing agent is 0.23:0.3.

[0016] Furthermore, the lithium source, nickel source, cobalt source and manganese source are respectively lithium acetate, nickel acetate, cobalt acetate and manganese acetate; and the complexing agent is citric acid monohydrate.

[0017] Furthermore, the mass ratio of the lithium-rich manganese positive electrode material powder to the P source is 1:25.

[0018] Furthermore, the nitrogen gas flow rate is 50 mL / min, and the heating rate of the tubular furnace is 5° C. / min.

[0019] Furthermore, in step 2, the inlet temperature of the spray drying is 230° C., the outlet temperature is 115° C., the peristaltic pump speed is 600-800 mL / h, the needle passing frequency is 15 Hz, and the spray pressure is 0.1-0.5 MPa; the atmosphere for the spray drying is air or oxygen.

[0020] Furthermore, the P source is sodium hypophosphite.

[0021] The invention discloses an application of a P-element coated lithium-rich manganese-based positive electrode material in a positive electrode of a lithium-ion battery.

[0022] The invention discloses an application of a P-element coated lithium-rich manganese-based positive electrode material in a positive electrode of a lithium-ion battery, characterized in that the preparation process of the lithium-ion battery positive electrode comprises: mixing the coated lithium-rich manganese-based positive electrode material, a conductive agent SuperP and a binder sodium carboxymethyl cellulose CMC into a slurry in a mass ratio of 85:10:5, and coating the slurry on an aluminum foil current collector to obtain a positive electrode sheet.

[0023] The beneficial effects of the present invention are:

[0024] (1) The separate sintering method is adopted to achieve uniform coating of P element while simplifying the process, and at the same time does not affect the structural properties of lithium-rich manganese-based positive electrode materials. Compared with the traditional ball milling calcination process, it does not require ball milling and long-term stirring steps, simplifies the preparation process, and improves production efficiency.

[0025] (2) The present invention places the lithium-rich manganese-based positive electrode material and the P source into two crucibles for sintering. On the one hand, an appropriate amount of the P source is evenly coated on the surface of the lithium-rich manganese-based positive electrode material through gas circulation. On the other hand, the lithium-rich manganese-based positive electrode material and the P source are placed in different quartz crucibles, respectively, to avoid the influence of sodium hypophosphite on the structure of the lithium-rich manganese material. At the same time, the P element is more evenly coated on the surface of the material, achieving uniform coating of the P element, providing a fast channel for Li+, accelerating the migration rate, stabilizing the material structure, increasing the material charge and discharge specific capacity, and improving the cycle stability performance.

[0026] (3) The P-element-coated lithium-rich manganese-based positive electrode material prepared by the present invention has a first-cycle capacity of more than 311.63 mAh / g at 0.1C under a voltage of 4.8 V, and a capacity retention rate of 98.85% for 50 cycles; the first-cycle capacity under 1C conditions reaches 241.10 mAh / g, and the capacity retention rate for 500 cycles can reach 91.62%. The cycle stability performance and rate performance are significantly better than those of ordinary lithium-rich manganese positive electrode material batteries.

[0027] In summary, the preparation method of the P element coated lithium-rich manganese-based positive electrode material of the present invention not only simplifies the preparation process and improves production efficiency, but more importantly, realizes uniform coating of the P element and significantly improves the electrochemical performance of the material. Through a reasonable amount of P element coating, the electrochemical performance of the material can be significantly improved, providing a positive electrode material with excellent performance for lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 X-ray diffraction patterns of lithium-rich manganese-based positive electrode materials prepared in Example 1, Example 2 and Comparative Example 1 and Comparative Example 3 of the present invention;

[0029] Figure 2 This is an electron microscopy scanning element distribution diagram of the lithium-rich manganese-based positive electrode material prepared in Example 2 of the present invention;

[0030] Figure 3 The first cycle charge and discharge curve of the battery assembled with the lithium-rich manganese-based positive electrode material prepared in Comparative Example 1 of the present invention at 0.1C;

[0031] Figure 4 The first cycle charge and discharge curve of the battery assembled with the lithium-rich manganese-based positive electrode material prepared in Example 1 of the present invention at 0.1C;

[0032] Figure 5 The first cycle charge and discharge curve of the battery assembled with the lithium-rich manganese-based positive electrode material prepared in Example 2 of the present invention at 0.1C;

[0033] Figure 6 This is a charge and discharge curve of the first cycle at 0.1C for a battery assembled with a lithium-rich manganese-based positive electrode material prepared in Comparative Example 3 of the present invention.

[0034] Figure 7 This is a 50-cycle curve diagram of a battery assembled with a lithium-rich manganese-based positive electrode material prepared in Comparative Example 1 of the present invention at 0.1C;

[0035] Figure 8 This is a 50-cycle curve diagram of a battery assembled with a lithium-rich manganese-based positive electrode material prepared in Example 1 of the present invention at 0.1C;

[0036] Fig. 9 This is a 50-cycle curve diagram of a battery assembled with a lithium-rich manganese-based positive electrode material prepared in Example 2 of the present invention at 0.1C;

[0037] Fig.10 The present invention is a 50-cycle curve diagram of a battery assembled with a lithium-rich manganese-based positive electrode material prepared in Comparative Example 3 at 0.1C;

[0038] Fig.11 The electrochemical performance cycle curve of the battery assembled with the lithium-rich manganese-based positive electrode material prepared in Comparative Example 1 of the present invention at 1C for 500 cycles;

[0039] Fig.12 The electrochemical performance cycle curve of the battery assembled with the lithium-rich manganese-based positive electrode material prepared in Example 1 of the present invention at 1C for 500 cycles;

[0040] Fig.13 The electrochemical performance cycle curve of the battery assembled with the lithium-rich manganese-based positive electrode material prepared in Example 2 of the present invention at 1C for 500 cycles;

[0041] Fig.14 The electrochemical performance cycle curve of the battery assembled with the lithium-rich manganese-based positive electrode material prepared in Comparative Example 3 of the present invention at 1C for 500 cycles;

[0042] Fig.15The cycle curves of the battery assembled with the lithium-rich manganese-based positive electrode material prepared in Comparative Example 1 of the present invention under different rate conditions (0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 10C);

[0043] Fig.16 The cycle curves of the battery assembled with the lithium-rich manganese-based positive electrode material prepared in Example 1 of the present invention under different rate conditions (0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 10C);

[0044] Fig.17 The cycle curves of the battery assembled with the lithium-rich manganese-based positive electrode material prepared in Example 2 of the present invention under different rate conditions (0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 10C);

[0045] Fig.18 The cycle curves of the battery assembled with the lithium-rich manganese-based positive electrode material prepared in Comparative Example 3 of the present invention under different rate conditions (0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 10C);

[0046] Fig.19 This is an electron microscope scanning image of the lithium-rich manganese-based positive electrode material electrode sheet prepared in Comparative Example 1 of the present invention before cycling and after cycling 500 cycles at 1C;

[0047] Fig. 20 This is an electron microscope scanning image of the lithium-rich manganese-based positive electrode material electrode sheet prepared in Example 2 of the present invention before cycling and after cycling 500 cycles at 1C. DETAILED DESCRIPTION

[0048] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0049] The present invention adopts a lithium-manganese-rich positive electrode material with a specific element composition, realizes the coating of the P element by calcining with a protective gas, adjusts the P element content, and realizes the structural modification of the lithium-manganese-rich positive electrode material.

[0050] Example 1

[0051] Step 1: Synthesize 0.5Li2MnO3·0.5Li(Ni 0.33 Co 0.33 Mn 0.33 )O2: 23.41 g of lithium acetate dihydrate, 6.16 g of nickel acetate tetrahydrate, 8.03 g of cobalt acetate tetrahydrate, and 22.60 g of manganese acetate tetrahydrate are dissolved in 1 L of deionized water, and then 63.042 g of citric acid monohydrate is added, and stirred on a magnetic stirrer for 1 hour to obtain a precursor solution;

[0052] Step 2: Pump the precursor solution into a spray dryer, select an inlet air temperature of 230°C, an outlet air temperature of 115°C, a peristaltic pump speed of 600-800 ml / h, a needle passing frequency of 15 Hz, a spray pressure of 0.2 MPa, and spray dry in an air atmosphere to obtain a precursor powder;

[0053] Step 3: Collect the precursor powder, put it in a corundum boat, put it into a crucible and calcine it in a muffle furnace at a heating rate of 3°C / min. After heating to 1000°C, keep the temperature for 20 minutes, during which air is continuously introduced into the muffle furnace. After cooling with the furnace, a lithium-rich manganese-based layered oxide (LRMO) is obtained;

[0054] Step 4: Place lithium-rich manganese-based layered oxide (LRMO) and sodium hypophosphite in two different quartz crucibles at a mass ratio of 1:20.

[0055] Step 5, placing a quartz crucible into a tubular furnace, placing the quartz crucible containing sodium hypophosphite on the air inlet side, and placing the quartz crucible containing lithium-manganese-based layered oxide on the air outlet side of the tubular furnace; opening the vent valve to continuously introduce nitrogen, setting the gas flow rate to 50 mL / min, setting the calcination temperature to 250°C, setting the calcination temperature to 250°C, the heating rate to 5°C / min, and calcining at 250°C for 1 hour;

[0056] Step 6: After the calcination is completed, the furnace is cooled and nitrogen gas is continuously introduced until it cools to room temperature and then turned off. Subsequently, the heating switch of the tubular furnace is turned off, and the crucible is taken out to obtain a lithium-rich manganese-based positive electrode material coated with P element, which is recorded as (20P-LRMO).

[0057] Example 2

[0058] Step 1: Synthesize 0.5Li2MnO3·0.5Li(Ni 0.33 Co 0.33 Mn 0.33 )O2: 23.41 g of lithium acetate dihydrate, 6.16 g of nickel acetate tetrahydrate, 8.03 g of cobalt acetate tetrahydrate, and 22.60 g of manganese acetate tetrahydrate are dissolved in 1 L of deionized water, and then 63.042 g of citric acid monohydrate is added, and stirred on a magnetic stirrer for 1 hour to obtain a precursor solution;

[0059] Step 2: Pump the precursor solution into a spray dryer, select an inlet air temperature of 230°C, an outlet air temperature of 115°C, a peristaltic pump speed of 600-800ml / h, a needle passing frequency of 15Hz, a spray pressure of 0.2MPa, and spray dry to obtain a precursor powder;

[0060] Step 3: Collect the precursor powder, put it in a corundum boat, put it into a crucible and calcine it in a muffle furnace at a heating rate of 3°C / min. After heating to 1000°C, keep the temperature for 20 minutes, during which air is continuously introduced into the muffle furnace. After cooling with the furnace, a lithium-rich manganese-based layered oxide (LRMO) is obtained;

[0061] Step 4: Place lithium-rich manganese-based layered oxide (LRMO) and sodium hypophosphite in two different quartz crucibles at a mass ratio of 1:25.

[0062] Step 5, placing a quartz crucible into a tubular furnace, placing the quartz crucible containing sodium hypophosphite on the air inlet side, and placing the quartz crucible containing lithium-manganese-based layered oxide on the air outlet side of the tubular furnace; opening the vent valve to continuously introduce nitrogen, setting the gas flow rate to 50 mL / min, setting the calcination temperature to 250°C, setting the calcination temperature to 250°C, the heating rate to 5°C / min, and calcining at 250°C for 1 hour;

[0063] (1) Step 6: After the calcination is completed, the furnace is cooled and nitrogen gas is continuously introduced until it cools to room temperature and then turned off. The heating switch of the tubular furnace is then turned off and the crucible is taken out to obtain a lithium-rich manganese-based positive electrode material coated with P element, which is recorded as (25P-LRMO). The element distribution of the lithium-rich manganese-based positive electrode material prepared in this embodiment is shown in the electron microscopy surface scanning. Figure 2 As shown in the figure, it can be seen that the P element is evenly distributed on the surface of the lithium-rich manganese particles to form a coating, but compared with other elements, its content is relatively small, so the X-ray diffraction did not detect its diffraction peak.

[0064] Comparative Example 1, without adding sodium hypophosphite

[0065] Step 1: Synthesize 0.5Li2MnO3·0.5Li(Ni 0.33 Co 0.33 Mn 0.33 )O2: 23.41 g of lithium acetate dihydrate, 6.16 g of nickel acetate tetrahydrate, 8.03 g of cobalt acetate tetrahydrate, and 22.60 g of manganese acetate tetrahydrate are dissolved in 1 L of deionized water, and then 63.042 g of citric acid monohydrate is added, and stirred on a magnetic stirrer for 1 hour to obtain a precursor solution;

[0066] Step 2: Pump the precursor solution into a spray dryer, select an inlet air temperature of 230°C, an outlet air temperature of 115°C, a peristaltic pump speed of 600-800ml / h, a needle passing frequency of 15Hz, a spray pressure of 0.2MPa, and spray dry to obtain a precursor powder;

[0067] Step 3: Collect the precursor powder, put it in a corundum boat, put it into a crucible and calcine it in a muffle furnace at a heating rate of 3°C / min. After heating to 1000°C, keep the temperature for 20 minutes, during which air is continuously introduced into the muffle furnace. After cooling with the furnace, a lithium-rich manganese-based layered oxide (LRMO) is obtained;

[0068] Step 4, placing a quartz crucible into a tubular furnace, placing the quartz crucible containing the lithium-rich manganese-based layered oxide on the gas outlet side of the tubular furnace; opening the vent valve to continuously introduce nitrogen, setting the gas flow rate to 50 ml / min, setting the calcination temperature to 250°C, the heating rate to 5°C / min, and calcining at 250°C for 1 hour;

[0069] Step 5: After the calcination is completed, the furnace is cooled and nitrogen gas is continuously introduced until it cools to room temperature and then closed. The crucible is taken out to obtain a lithium-rich manganese-based positive electrode material that is not coated with the P element, which is recorded as (LRMO).

[0070] Comparative Example 2

[0071] Step 1: Synthesize 0.5Li2MnO3·0.5Li(Ni 0.33 Co 0.33 Mn 0.33 )O2: 23.41 g of lithium acetate dihydrate, 6.16 g of nickel acetate tetrahydrate, 8.03 g of cobalt acetate tetrahydrate, and 22.60 g of manganese acetate tetrahydrate are dissolved in 1 L of deionized water, and then 63.042 g of citric acid monohydrate is added, and stirred on a magnetic stirrer for 1 hour to obtain a precursor solution;

[0072] Step 2: Pump the precursor solution into a spray dryer, select an inlet air temperature of 230°C, an outlet air temperature of 115°C, a peristaltic pump speed of 600-800ml / h, a needle passing frequency of 15Hz, a spray pressure of 0.2MPa, and spray dry to obtain a precursor powder;

[0073] Step 3: Collect the precursor powder, put it in a corundum boat, put it into a crucible and calcine it in a muffle furnace at a heating rate of 3°C / min. After heating to 1000°C, keep the temperature for 20 minutes, during which air is continuously introduced into the muffle furnace. After cooling with the furnace, a lithium-rich manganese-based layered oxide (LRMO) is obtained;

[0074] Step 4: Place lithium-rich manganese-based layered oxide (LRMO) and sodium hypophosphite in two different quartz crucibles at a mass ratio of 1:5.

[0075] Step 5, placing a quartz crucible into a tubular furnace, placing the quartz crucible containing sodium hypophosphite on the air inlet side, and placing the quartz crucible containing lithium-manganese-based layered oxide on the air outlet side of the tubular furnace; opening the vent valve to continuously introduce nitrogen, setting the gas flow rate to 50 mL / min, setting the calcination temperature to 250°C, setting the calcination temperature to 250°C, the heating rate to 5°C / min, and calcining at 250°C for 1 hour;

[0076] Step 6. After the calcination is completed, the furnace is cooled and nitrogen gas is continuously introduced until it cools to room temperature and then turned off. Subsequently, the heating switch of the tubular furnace is turned off, and the crucible is taken out to obtain a lithium-rich manganese-based positive electrode material coated with P element, which is recorded as (5P-LRMO).

[0077] Comparative Example 3

[0078] Step 1: Synthesize 0.5Li2MnO3·0.5Li(Ni 0.33 Co 0.33 Mn 0.33 )O2: 23.41 g of lithium acetate dihydrate, 6.16 g of nickel acetate tetrahydrate, 8.03 g of cobalt acetate tetrahydrate, and 22.60 g of manganese acetate tetrahydrate are dissolved in 1 L of deionized water, and then 63.042 g of citric acid monohydrate is added, and stirred on a magnetic stirrer for 1 hour to obtain a precursor solution;

[0079] Step 2: Pump the precursor solution into a spray dryer, select an inlet air temperature of 230°C, an outlet air temperature of 115°C, a peristaltic pump speed of 600-800ml / h, a needle passing frequency of 15Hz, a spray pressure of 0.2MPa, and spray dry to obtain a precursor powder;

[0080] Step 3: Collect the precursor powder, put it in a corundum boat, put it into a crucible and calcine it in a muffle furnace at a heating rate of 3°C / min. After heating to 1000°C, keep the temperature for 20 minutes, during which air is continuously introduced into the muffle furnace. After cooling with the furnace, a lithium-rich manganese-based layered oxide (LRMO) is obtained;

[0081] Step 4: Place lithium-rich manganese-based layered oxide (LRMO) and sodium hypophosphite in two different quartz crucibles at a mass ratio of 1:30.

[0082] Step 5, placing a quartz crucible into a tubular furnace, placing the quartz crucible containing sodium hypophosphite on the air inlet side, and placing the quartz crucible containing lithium-manganese-based layered oxide on the air outlet side of the tubular furnace; opening the vent valve to continuously introduce nitrogen, setting the gas flow rate to 50 mL / min, setting the calcination temperature to 250°C, setting the calcination temperature to 250°C, the heating rate to 5°C / min, and calcining at 250°C for 1 hour;

[0083] Step 6. After the calcination is completed, the furnace is cooled and nitrogen gas is continuously introduced until it cools to room temperature and then turned off. Subsequently, the heating switch of the tubular furnace is turned off, and the crucible is taken out to obtain a lithium-rich manganese-based positive electrode material coated with P element, which is recorded as (30P-LRMO).

[0084] Test analysis:

[0085] The positive electrode material (the lithium-rich manganese positive electrode material coated with P element of Example 1, Example 2 and Comparative Examples 2-3 or the lithium-rich manganese positive electrode material of Comparative Example 1), a conductive agent (SuperP), and a binder (sodium carboxymethyl cellulose CMC) are mixed into a slurry in a mass ratio of 85:10:5. The stirring rate is 500 rad / min and the stirring is uniform. Then, a scraper is used to coat the slurry on an aluminum foil current collector to obtain a positive electrode sheet. The scraper thickness is 0.2 mm. The vacuum oven temperature is 110°C and the time is 20 h to obtain a lithium-rich manganese-based positive electrode sheet.

[0086] The lithium-rich manganese-based positive electrode sheets were cut into round pieces of uniform size, dried, and assembled into 2025 button batteries in a glove box filled with argon gas with oxygen and water content less than 0.01ppm. The button batteries were placed in an oven for long-term activation treatment at a temperature of 45°C and a treatment time of 40h. After being taken out, the battery cycle performance test was carried out at different current densities.

[0087] Electrochemical performance The charge and discharge test of 2025 button cells was carried out on the Xinwei test system, with metal Li sheets as reference electrodes and counter electrodes, Celgard-2400 as the diaphragm, Xinzhoubang 3045I as the electrolyte, and the test voltage window of 2.0-4.8V. The test temperature was 27±1℃, and the first three cycles were activated at a rate of 0.1C (1C=200mAh / g), and the 1C rate cycle was used from the 4th cycle. The performance test results are shown in Table 1.

[0088] Table 1

[0089]

[0090] It can be seen from Table 1 that too little P element coating (5P) in comparative example 2 does not have a significant effect on the performance, and there is almost no change. The appropriate amount of P element coating (25P) in Example 2 greatly improves the charge and discharge specific capacity and cycle stability of the material, while the excessive P element doping (30P) in comparative example 3 causes the Li+ mobility to be blocked after the coating layer, and the electrochemical performance of the battery is reduced. Therefore, the battery prepared by the lithium-rich manganese-based positive electrode material of the present invention: sodium hypophosphite = 1:25 (25P-LRMO) has the best electrochemical performance, and the first discharge capacity at 0.1C can reach 311.63mAh / g, and the capacity retention rate after 50 cycles reaches more than 98.85%, and the first discharge capacity at 1C can reach 241.10mAh / g, and the capacity retention rate after 100 cycles reaches 89.07%.

[0091] like Figure 1 As shown, from the analysis of the X-ray diffraction results of Example 1, Example 2 and Comparative Example 1, Comparative Example 3, it can be seen that the doping of P element does not cause the change of the lithium-rich manganese layered structure, and the addition of surface P element has no effect on the internal structure of the lithium-rich manganese positive material, and is mainly distributed on the surface of the lithium-rich manganese particles. However, the presence of P element is not found in the XRD spectrum, which may be due to the low content of P element, resulting in the detection result is not significant.

[0092] like Figure 3-6 As shown, from the first cycle charge and discharge curve data of Example 1, Example 2 and Comparative Examples 1 and 3 at 0.1C, it can be seen that the coating of an appropriate amount of P element significantly improves the first cycle discharge specific capacity of the lithium-rich manganese positive electrode material, and the P element coating provides a fast channel for Li+ migration, while excessive P element doping increases the coating thickness, inhibits the migration of Li+, and thereby reduces the discharge specific capacity.

[0093] like Figure 7-10 As shown, from the electrochemical performance cycle curves of Example 1, Example 2 and Comparative Example 1 and Comparative Example 3 at 0.1C, it can be seen that the positive electrode material battery prepared with lithium-rich manganese material: sodium hypophosphite = 1:25 (25P-LRMO) has the best capacity retention rate after 50 cycles, which is as high as 98.85%.

[0094] like Figure 11-14 As shown, from the electrochemical cycle curves of Example 1, Example 1 and Comparative Example 3 for 500 cycles under 1C conditions, it can be seen that the coating of P element not only improves the charge and discharge capacity of the battery, but also significantly improves its battery cycle stability performance. Appropriate P element doping makes the capacity retention rate of the battery reach 91.62% after 500 cycles at 1C. Excessive P element will cause a slight decrease in the battery cycle stability, but it is still better than the electrochemical performance of the uncoated lithium-manganese-rich positive electrode material.

[0095] like Figure 15-18 As shown, from the rate performance curves of Example 1, Example 2 and Comparative Example 1 and Comparative Example 3 at 1C, it can be seen that as the test current gradually increases, the battery discharge capacity gradually decreases, and the 25P-LRMO lithium-rich manganese positive electrode material has the highest discharge capacity. When the current density is reduced from 10C to 0.1C, its discharge capacity reaches 300mAh / g, with a good capacity retention rate.

[0096] like Fig.19 and Fig. 20 As shown in the electron microscope scanning images of the positive electrode sheets of Example 2 and Comparative Example 1 after 500 cycles at 1C, the surface of the lithium-rich manganese particles coated with P element appears dark gray due to the P element coating layer. The lithium-rich manganese positive electrode sheets that have not been coated have all broken after 500 cycles, and the overall structure of the particles has collapsed to form clusters. The lithium-rich manganese positive electrode sheets treated with lithium-rich manganese: sodium hypophosphite = 1:25 still maintain good integrity after 500 cycles, and the particle structure has not changed significantly, which has good structural stability.

[0097] In summary, embodiment 2 is the best embodiment.

[0098] The above are only specific embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a P-element coated lithium-rich manganese-based positive electrode material, characterized in that: The following steps are involved: Step 1: dissolving a lithium source, a nickel source, a cobalt source, and a manganese source in water at a molar ratio of Li:Ni:Co:Mn=1.53:0.165:0.165:0.665, and adding a complexing agent to obtain a precursor solution; Step 2: obtaining a precursor powder of the material by high temperature spray drying the precursor solution; Step 3: sintering the precursor powder at 1000° C. for 20 min to obtain a lithium-rich manganese positive electrode powder material; Step 4: Put the lithium-rich manganese cathode material powder obtained in step 3 and the P source into two different quartz crucibles according to a mass ratio of 1:20-1:25; Step 5: Put two quartz crucibles respectively filled with lithium-rich manganese powder and P source into a tube furnace for sintering, the crucible filled with P source is placed near the air inlet side, and the crucible filled with lithium-rich manganese powder is placed near the air outlet side; Step 6: Open the gas valve of the tubular furnace and continue to introduce nitrogen; calcine at 250°C for 1 hour, and after natural cooling, obtain a lithium-rich manganese-based positive electrode material coated with P element.

2. The method for preparing the P element coated lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In step 1, the molar volume ratio of lithium ions in the lithium source to water is 0.23 mol / L.

3. The method for preparing the P element coated lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In step 1, the molar ratio of lithium ions in the lithium source to the complexing agent is 0.23:0.

3.

4. The method for preparing the P element coated lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The lithium source, nickel source, cobalt source and manganese source are respectively lithium acetate, nickel acetate, cobalt acetate and manganese acetate, and the complexing agent is citric acid monohydrate.

5. The method for preparing the P element coated lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The mass ratio of the lithium-rich manganese positive electrode material powder to the P source is 1:

25.

6. The method for preparing the P element coated lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The nitrogen gas flow rate was 50 mL / min, and the heating rate of the tubular furnace was 5° C. / min.

7. The method for preparing a P-element coated lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In step 2, the inlet temperature of the spray drying is 230°C, the outlet temperature is 115°C, the peristaltic pump speed is 600-800mL / h, the needle passing frequency is 15Hz, and the spray pressure is 0.1-0.5MPa; the atmosphere of the spray drying is air or oxygen.

8. The method for preparing a P-element coated lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The P source in step 4 is sodium hypophosphite.

9. Use of the P-element doped and coated lithium-rich manganese-based positive electrode material as claimed in claim 1 in a positive electrode of a lithium-ion battery.

10. The use of the P-element doped and coated lithium-rich manganese-based positive electrode material in a positive electrode of a lithium-ion battery according to claim 9, characterized in that: The preparation process of the lithium-ion battery positive electrode comprises: mixing a coated lithium-rich manganese-based positive electrode material, a conductive agent SuperP and a binder sodium carboxymethyl cellulose CMC into a slurry in a mass ratio of 85:10:5, and coating the slurry on an aluminum foil current collector to obtain a positive electrode sheet.